(untitled) (Revista Apotheke, 2025)
The interview presents reflections by the artist and researcher José Carlos da Rocha, PhD in Visual Arts from the State University of Santa Catarina, on how art, revealed in maturity, fosters processes of academic and scientific development. The dialogue traces his trajectory from economics to painting, highlighting the significance of his artistic production, research, teaching experience, and contributions to the fields of contemporary art and visual arts education.